2013
DOI: 10.7567/jjap.53.018001
|View full text |Cite
|
Sign up to set email alerts
|

Misfit dislocation anisotropies in the InGaAs/GaAs(001) interface measured using X-ray topography and reciprocal space mapping

Abstract: The anisotropies of misfit dislocations (MDs) formed at an InGaAs/GaAs(001) interface grown by molecular beam epitaxy were investigated using X-ray topography and X-ray reciprocal space mapping techniques. The MDs bunched in small regions to form MD bunches. The number of MDs running along the direction (α-MDs) included in one MD bunch was larger than that along the [110] direction (β-MDs). In addition, the bunched α-MDs were aligned more periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The calculated critical thickness was seven times lower than the thickness of the AR of structure B -1.613 mm. Yastrubchak et al (2004) and Suzuki et al (2014) showed that for In x Ga 1Àx As layers on a GaAs substrate there are two types of misfit dislocations, and , which lie along the [ " 1 110] and [110] directions, respectively. Anisotropy of the dislocation density was observed for these two directions.…”
Section: Strain Relaxation and Dislocation Density From Analysis Of Dmentioning
confidence: 99%
“…The calculated critical thickness was seven times lower than the thickness of the AR of structure B -1.613 mm. Yastrubchak et al (2004) and Suzuki et al (2014) showed that for In x Ga 1Àx As layers on a GaAs substrate there are two types of misfit dislocations, and , which lie along the [ " 1 110] and [110] directions, respectively. Anisotropy of the dislocation density was observed for these two directions.…”
Section: Strain Relaxation and Dislocation Density From Analysis Of Dmentioning
confidence: 99%